Quantum statistics of bosonic cascades - Liew, Timothy Chi Hin (2017)
Bosonic cascades formed by lattices of equidistant energy levels sustaining radiative transitions between nearest layers represent a unique system to study correlated optical phenomena. We show how the light emitted by condensates in the visible range introduces a new regime of emission for cascade systems. Namely, the quantum statistics of bosonic cascades exhibits superbunching plateaus. This demonstrates further potentialities of bosonic cascade lasers for the engineering of correlated properties of light useful for imaging applications.